Online media’s role in public health information and communication sharing in Cote d’Ivoire (Ivory coast) - Abdoulaye, Ousmane Koffi; Zanuddin, Hasmah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The effects of health communication interventions are to reach a large number of individuals and communities, as Rogers and Storey, (1987) stated that these are possible within a specified period of time and through an organized set of communication activities. Hence, to promote vaccination and its well-being through health communication campaigns, as in the United States it requires efforts to inform the public about infectious diseases and the benefits of immunization (Paisley, 2001). Nowadays, health communication campaigns and interventions have used a variety of ways to send healthcare messages. However, the role and effectiveness of health communication has been discussed recently without information and communication technologies (ICTs) in improving health systems and healthcare services, particular in the developing countries, including Cote d’Ivoire. The hospitals in Cote d’Ivoire were lacking proper medical infrastructures, or they had outdated equipment. This has revealed the vulnerability of a few healthcare issues, such as HIV/AIDS, tuberculosis, malaria, etc. as they are quite widespread among the population. © BEIESP.